Differences in the speed and power of elite U12 and U13 Croatian soccer players - Mikic, L.; Marasovic, J.; Rada, A.; Erceg, M.; Sivric, H. (SportMont, 2024)
Identification of talent and continuous evaluation of players` abilities is an indispensable part of the selection process. The main goal of the research was to determine the differences in speed and power of elite U12 and U13 young Croatian soccer players with different roles in the team. Out of the 38 total HNK Hajduk Split players, 18 players were U12 age category while 20 players were U13 age category. Players were divided by the coaches in the groups of higher quality (key players) and lower quality (rotation players). Players were tested with 2 tests to assess explosive power and 3 tests to assess speed. Results obtained with Student`s T-test showed that there are no significant differences in the speed and the power between the two observed group of players for each age category. For U12 category key players demonstrated better results than rotation players in the standing long jump and the medicine ball throw (183.89/566.44 vs. 177.22/511.89 cm, respectively). Additionally, key players performed better in 5-, 10- and 20- m sprint (1.11/1.93/3.43 vs. 1.14/1.96/3.52 s). U13 key players performed similar with rotation players in 5-, 10- and 20- m sprint (1.12/1.97/3.44 vs. 1.13/1.97/3.47 s), but interestingly, U13 key players were slightly worse than rotation players in the standing long jump and the medicine ball throw (194.33/587.67 vs. 194.75/606.50 cm). Many variables and abilities may determine soccer success. For the observed participants it seems likely that other abilities could have been more decisive for status differentiation in the team.